Primary portal vein hypoplasia with portal hypertension in a young dog - KASABALIS (Δ. ΚΑΣΑΜΠΑΛΗΣ), D.; ALATZAS (Δ. ΑΛΑΤΖΑΣ), D.; ALATZA (Δ. ΑΛΑΤΖΑ), D.; PETANIDES (Θ. ΠΕΤΑΝΙΔΗΣ), T. A.; ALATZAS (Γ. ΑΛΑΤΖΑΣ), G.; PAPAZOGLOU (Λ. ΠΑΠΑΖΟΓΛΟΥ), L. G.; HARLEY, R.; MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ), M. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 5-month old Caucasian dog was presented with a 20-day history of abdominal distention along with inappetance, depression and vomiting of 24-hour duration. Physical examination findings included depression, ascites, mild inspiratory dyspnea and dehydration. Clinicopathological evaluation revealed hyperammonemia, hypoalbuminemia, hyperbilirubinemia, hypoglycemia and hyponatremia. Μicrohepatia and free abdominal fluid was detected with abdominal ultrasonography. During exploratory laparotomy, multiple acquired portosystemic collateral vessels were found, indicative of portal hypertension, along with a small liver of normal color and texture. Liver histopathology included features consistent with liver hypoperfusion. These findings supported the diagnosis of primary portal vein hypoplasia with portal hypertension. The animal recovered uneventfully postoperatively and was discharged with diuretics, hepatoprotectants and a low-protein diet and remains healthy two years after diagnosis. This case underscores that a favorable prognosis may be anticipated in cases of primary portal vein hypoplasia with portal hypertension, thus, justifying the long-term conservative management instead of considering euthanasia.